2007
DOI: 10.1007/s10194-007-0368-9
|View full text |Cite
|
Sign up to set email alerts
|

Contractile responses to ergotamine and dihydroergotamine in the perfused middle cerebral artery of rat

Abstract: The vasomotor effects of ergotamine and dihydroergotamine (DHE) on the middle cerebral artery (MCA) of rats were studied using the pressurised arteriography method and in vitro myographs. MCAs from Sprague-Dawley rats were mounted on two glass micropipettes using the arteriograph, pressurised to 85 mmHg and luminally perfused. All vessels used attained spontaneous contractile tone (34.9±1.8% of resting tone) and responded to luminal adenosine triphosphate (ATP) with dilatation (24.1±4.0%), which showed functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…If a drug has an effect both luminal and abluminal it will usually be because the drug can cross the BBB of the artery provided the endothelium is intact (checked at the start of the experiments). This is the case for ergotamine and dihydroergotamine (DHE), which both result in quite similar contractile responses when given luminally or abluminally (49). In agreement, Goadsby found tritium-labelled DHE in the brainstem of cats following systemic administration (50).…”
Section: Consequences Of Preserved Bbb For Migraine Treatmentmentioning
confidence: 96%
“…If a drug has an effect both luminal and abluminal it will usually be because the drug can cross the BBB of the artery provided the endothelium is intact (checked at the start of the experiments). This is the case for ergotamine and dihydroergotamine (DHE), which both result in quite similar contractile responses when given luminally or abluminally (49). In agreement, Goadsby found tritium-labelled DHE in the brainstem of cats following systemic administration (50).…”
Section: Consequences Of Preserved Bbb For Migraine Treatmentmentioning
confidence: 96%
“…In a second series of experiments, canine femoral veins incubated for 10 min with DHE (2 × 10 −7 M) elicited a slow, concentration-dependent increase in tension, which could not be eliminated by changing the bathing solution every 7.5 min for two h (Figure 5) (34). In an in vitro study using the middle cerebral artery of rats, DHE caused a slow onset of a contractile response with a time to maximum of 25–32 min (35). Repeated flushing of the bath caused a return to baseline 13–48 min after initiating the washing (35).…”
Section: Pharmacological Investigations Of Time-effect Curves Of Dhementioning
confidence: 99%
“…The problem of recurrence (after an initial response the migraine pain recurs) after subcutaneous sumatriptan treatment was first observed by Iversen in Denmark in 1989 (104); and in RCTs it has been found that oral and rectal ergotamine (51) and subcutaneous dihydroergotamine (105) caused less, in most cases 50% less, recurrence than the triptans (51, 52). This is most likely due to tight binding of ergot alkaloids to the vascular receptor (106).…”
Section: Bioavailability and Working Mechanism Of Ergotaminementioning
confidence: 99%